The EU strategy for Central Asia and Kyrgyzstan foreign policy - Nazira Momosheva (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2010)
[Introduction] The change of the strategic significance of Central Asia in last two decades had considerable consequences on the domestic and foreign policies in the region. The newly independent Central Asian states became a target of interplay between political and economic interests of several countries. The formation of the foreign policies in Central Asian states takes place under extremely difficult conditions and aims to balance between different powers. Historically, Central Asia has very close links with Russia. In addition, there are some other actors like United States, European Union, Turkey, Iran, Pakistan, China, India and several Middle Eastern states, playing important role in the region. Their participation adds to the development of international relations in the region a comprehensive and de-facto global dimension. The primary goal of the countries in Central Asia is the closer involvement into the world integration processes, as well as solution of the intra-relationship problems, influenced by surrounding neighbors: Afghanistan, Pakistan, Iran, China and India. There is a highly controversial discussion among the political experts about the future of Central Asia. Some scientists believe that the region will remain the part of the Eurasian space. Some researchers consider the future prospects of the region to be limited due to factors like lack of direct access to global communications, low military capabilities, etc. (...)
Keywords: 330